CENOMANIAN-TURONIAN RADIOLARIANS OF NORTHERN TURKEY AND THE CRIMEAN MOUNTAINS - Bragina L.G. (My University, 2004)
The Middle Cenomanian-Early Turonian radiolarians are studied from two sections of the central Pontic Mountains (northern Turkey) and three sections of the Crimean Mountains. The type section of the Tomalar Formation (Turkey) contains a Middle-Early Cenomanian assemblage with Dactyliosphaera silviae, correlative to the upper part of the Dactyliosphaera silviae Zone in the western Mediterranean. The Urküt sec-tion (Turkey) yielded a rich assemblage with species characteristic of the Dactyliosphaera silvae Zone. In the Crimean Mountains there are two radiolarian assemblages (from the base upward): (1) Triactoma parva-Patu-libracchium ingens Assemblage (Late Cenomanian), which corresponds to the upper part of the Dactyl-iosphaera silvae Zone, and (2) Alievium superbum Assemblage (Early Turonian), which corresponds to the Alievium superbum circumtropical Zone. These radiolarian assemblages are compared with those known from the literature, and the stratigraphic ranges of these radiolarians are revised. Descriptions of 193 species belong-ing to 4 orders, 28 families, and 77 genera are given. These include 1 genus and 3 species that were previously erected by the author and descriptions of 1 new genus and 36 new species. Diagnoses of 5 genera and 28 species are emended. Most of the stratigraphic and geographic ranges of these radiolarians are more precisely delimited.
Keywords: Radiolaria; Nassellaria; Spumellaria; stratigraphy; Upper Cretaceous; Crimean Mountains; northern Turkey; systematics; Mesozoic::Cretaceous::Upper::Turonian; Мезозой::Меловая::Верхний::Туронский; Мезозой::Меловая::Верхний::Сеноманский; Mesozoic::Cretaceous::Upper::Cenomanian